1992
DOI: 10.1007/bf00010975
|View full text |Cite
|
Sign up to set email alerts
|

Root dynamics in plant and ratoon crops of sugar cane

Abstract: The root system of a sugar cane crop on an Ultisol in northeastern Brazil was examined throughout the plant and first ratoon crop cycles, using both coring and minirhizotron methods. Total root masses (living plus dead, 0.9-1.1 kg m -2) and live root lengths (14.0-17.5 km m -2) were greater during the ratoon cycle than at the end of the plant cane cycle (0.75 kg m 2 and 13.8 km m -2, respectively ). Root die-back during the two weeks following ratoon harvest was estimated to be 0.15 kg m -, about 17% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2
13

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 21 publications
(17 reference statements)
3
45
2
13
Order By: Relevance
“…Chopart et al (1998) found a large range of SRLs (from 7 m g -1 to 91 m g -1 ) measured at 45 and 113 DAP down to a depth of 1.1 m in the Ivory Coast. Ball-Coelho et al (1992) found SRLs near 16.5 m g -1 in northeastern Brazil for the plant and fi rst ratoon crop cycles.…”
Section: Parameter Estimationmentioning
confidence: 94%
See 1 more Smart Citation
“…Chopart et al (1998) found a large range of SRLs (from 7 m g -1 to 91 m g -1 ) measured at 45 and 113 DAP down to a depth of 1.1 m in the Ivory Coast. Ball-Coelho et al (1992) found SRLs near 16.5 m g -1 in northeastern Brazil for the plant and fi rst ratoon crop cycles.…”
Section: Parameter Estimationmentioning
confidence: 94%
“…14, derived from the results of Jones & Kiniry (1998) and Ball-Coelho et al (1992). (14) where RootSene is the percentage of total root senesced each day, and WR is the total root dry mass (g m -2 ) [ground basis].…”
Section: Crop Componentsmentioning
confidence: 99%
“…To Inforzato & ALVAREZ (1957), 59% of the roots are in 0.30 m surface. BALL-COELHO et al (1992) found that 62.70% of the numbers of roots are located at a depth of 0.00 to 0.50 m.…”
Section: Effective Root Depthmentioning
confidence: 98%
“…Unfortunately, there is no recent data about the assessment of sugarcane root system using non-destructive methods, such as minirhizotrons, which allow the monitoring of root growth along the crop cycle under field conditions. In fact, the only study with minirhizotron in sugarcane crop was carried out by Ball-Coelho et al (1992) under rainfed conditions.…”
Section: Introductionmentioning
confidence: 99%